An Examination of the effect of impact investment instruments on sustainable development financing in Kenya - Mati, Benson Njiru (Strathmore University, 2021)
It is estimated that the amount of finances required for key sectors related to the United Nations 2030 Agenda for Sustainable Development at the global level is approximately US dollar 5 to 7 trillion per year. This study sought to break ground in a new academic field of enquiry by examining the effect of impact investment instruments, novel approach for financing social and sustainable enterprises that is gaining momentum in Kenya and across the world, on sustainable development financing in Kenya. This study sought empirical evidence on the effect of green bonds and social impact bonds (SIBs) usage on sustainable development financing in Kenya. The 2030 Agenda for Sustainable Development overall vision is to lead the world toward a path of inclusive economic development, social inclusion and environmental sustainability. The study sought to examine Kenya’s progress in sustainable development financing and took stock of the effect of impact investment instruments on financing social and sustainable enterprises implementing the SDGs commitments in Kenya. The study empirically analysed social, environmental and economic performance data from impact investors employees in Kenya and mapped the impact data to the SDGs. Using a descriptive cross-sectional survey design, relevant data was collected from 185 employees of the 37 impact investors, members of GIIN, using structured questionnaires and analysed using descriptive and inferential analysis. Results showed that impact investment instruments play a critical role in sustainable development financing in Kenya. Further, a statistically positive significant relationship between social impact bonds and sustainable development financing was found, while green bonds had a statistically negative significant relationship with sustainable development financing. Finally, the joint effect of the two variables was statistically significant. Theoretically, this study contributes to impact investment instruments knowledge base by providing a model that optimizes the use of impact investment instruments on sustainable development financing. The study provides empirical evidence supporting the structure of impact investment instruments and sustainable development financing link from a developing country context using perspectives of the impact investors’ employees. Policy formulation may focus on mandating impact investors to develop social and environment performance management practices for measuring and reporting their social and environment performance.
A Dissertation submitted to Strathmore Business School in Partial fulfillment of the requirements for the award of Master of Science in Development Finance Degree of Strathmore University
Keywords: Financing; Green bonds; Impact investment; SIBs; Sustainable development